Huntingtin gene CAG repeat size affects autism risk: Family‐based and case–control association study. Issue 6 (11th July 2020) - Piras, Ignazio Stefano; Picinelli, Chiara; Iennaco, Raffaele; Baccarin, Marco; Castronovo, Paola; Tomaiuolo, Pasquale; Cucinotta, Francesca; Ricciardello, Arianna; Turriziani, Laura; Nanetti, Lorenzo; Mariotti, Caterina; Gellera, Cinzia; et al.
Abstract: The Huntingtin ( HTT ) gene contains a CAG repeat in exon 1, whose expansion beyond 39 repeats consistently leads to Huntington's disease (HD), whereas normal‐to‐intermediate alleles seemingly modulate brain structure, function and behavior. The role of the CAG repeat in Autism Spectrum Disorder (ASD) was investigated applying both family‐based and case–control association designs, with the SCA3 repeat as a negative control. Significant overtransmission of "long" CAG alleles (≥17 repeats) to autistic children and of "short" alleles (≤16 repeats) to their unaffected siblings (all p  < 10 −5 ) was observed in 612 ASD families (548 simplex and 64 multiplex). Surprisingly, both 193 population controls and 1, 188 neurological non‐HD controls have significantly lower frequencies of "short" CAG alleles compared to 185 unaffected siblings and higher rates of "long" alleles compared to 548 ASD patients from the same families ( p  < .05–.001). The SCA3 CAG repeat displays no association. "Short" HTT alleles seemingly exert a protective effect from clinically overt autism in families carrying a genetic predisposition for ASD, while "long" alleles may enhance autism risk. Differential penetrance of autism‐inducing genetic/epigenetic variants may imply atypical developmental trajectories linked to HTT functions, including excitation/inhibition imbalance, cortical neurogenesis and apoptosis, neuronal migration, synapse formation, connectivity and homeostasis.